2000
DOI: 10.1016/s0370-2693(00)00704-8
|View full text |Cite
|
Sign up to set email alerts
|

Spin alignment of mesons produced in neutron-carbon interactions

Abstract: A new precise measurements of spin density matrix element ρ 00 of K * (892) ± mesons produced inclusively in neutron-carbon interactions at ∼ 60 GeV have been carried out in the EXCHARM experiment at the Serpukhov accelerator. The values of ρ 00 obtained in the transversity frame are 0.424 ± 0.011(stat) ± 0.018(sys) for K * (892) + and 0.393 ± 0.025(stat) ± 0.018(sys) for K * (892) − . Significant P T dependence of ρ 00 has been observed in K * (892) + production.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…It has been shown that the existence of the spin alignment of vector mesons in unpolarized hadron-hadron collision is another manifestation of the existence of the s q · n type of spin correlation. The obtained result are in agreement with the available data [26,27,28].…”
Section: The Physical Picturesupporting
confidence: 92%
See 1 more Smart Citation
“…It has been shown that the existence of the spin alignment of vector mesons in unpolarized hadron-hadron collision is another manifestation of the existence of the s q · n type of spin correlation. The obtained result are in agreement with the available data [26,27,28].…”
Section: The Physical Picturesupporting
confidence: 92%
“…(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) to get the numerical results for P Λ (x F |s) as a function of x F .…”
Section: Resultsmentioning
confidence: 99%
“…In the past, spin alignment measurements in e þ e − [31][32][33], hadron-proton [34] and nucleon-nucleus collisions [35] were carried out to understand the role of spin in the dynamics of particle production, finding ρ 00 > 1=3 and off-diagonal elements close to zero with respect to the PP. For pp collisions at ffiffi ffi s p ¼ 13 TeV, we find ρ 00 ∼ 1=3…”
mentioning
confidence: 99%
“…Other elements, ρ 10 and ρ 1−1 , can be studied by further measuring W (θ, φ). In fact, such measurements have already been carried out in lepton induced reactions and hadron-hadron collisions [4,5,6,7,8,9,10,11,12,13,16,17,18]. Unlike the polarization of hyperons, the spin-alignment of vector mesons, ρ V 00 , does not know the direction of the reaction plane since it only depends on cos 2 θ [see Eq.…”
mentioning
confidence: 99%